Dictionary of civil engineering - Scott, John Somerville (Granada, 1981)
The book not only embraces the whole scope of civil and structural engineering but also includes, wherever relevant, the fields of drawing-office practice, electrical engineering, mining, photogrammetry, railways, sewage disposal, soil mechanics, statistics, structural design and topographical surveying